THE LIFE OF BULUH CINA FISHERMEN IN SIAK HULU DISTRICT KAMPAR CITY (CASE STUDY OF BULUH CINA VILLAGE) - Ilham Syahroni; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Communities in the Buluh Cina Village The relatively low socio-economic level of the people of the Village of Buluh Cina is one of the common characteristics of the life of fishermen there, although fishermen are the most common work done by the people of the Buluh Cina Village reed but the results obtained by being a fish fisherman are not so much that still not enough to fulfill daily life for the fishermen and their families. This study aims to determine To find out the inhibiting and supporting factors of the fishing community of Buluh Cina Village in living their daily lives, to find out the strategies of the fishing communities of Buluh Cina Village in living their daily lives. The benefits of this research are expected to be able to provide information, as the development of social sciences, as a guide or reference about the lives of fishermen. This research is a descriptive qualitative research with observation, interview and documentation techniques. This study uses the determination in determining the subjects in this study were selected using a purposive sampling technique. Purposive sampling is a technique used when specific informants are based on research objectives. The theory used is Social Capital theory. This study used 6 subjects. The results of this study found that most of the people in the village of Buluh Cina were fishermen who were made as the main source of their livelihood to meet the needs of their family lifeKeywords: Social, Economy, Fishermen, Social Capital